Optical image encryption scheme based on apertured fractional Mellin transform. (April 2020) - Wang, Mengmeng; Pousset, Yannis; Carré, Phillippe; Perrine, Clency; Zhou, Nanrun; Wu, Jianhua
Highlights: An optical image encryption scheme is proposed. The scheme is based on an apertured fractional Mellin transform. Realization is by log-polar transform and the apertured fractional Fourier transform. More free parameters make the encryption system possess a huge key space. The nonlinearity makes the encryption system be able to resist common attacks. Abstract: An optical image encryption scheme is proposed by utilizing an apertured nonlinear fractional Mellin transform (FrMT). Due to its nonlinear property, FrMT is utilized for eliminating potential insecurity in an image encryption system caused by known-plaintext and chosen-plaintext attacks. The aperture in the optical system makes it harder for attackers to collect optical signals in the transmission process. The apertured FrMT can be implemented by log-polar transform and Collins diffraction and the key space of the proposed image encryption algorithm is very large. The orders of the FrMT, the radii of the FrMT domains, the order of the FrFT, the phases generated in the further encryption process, wavelength, side-lengths of hard aperture, and the parameters of logistic map are used as cipher keys. Extensive simulation results demonstrate that the proposed algorithm is feasible, sensitive to the keys, and capable of resisting common classical attacks. The encryption effect changes with the size of apertures.